Optimizing The Culture Of Discipline Of Polri Members Based On Pp No 2 Of 2003 To Realize Professionalism - Biantoro, Prasojo Soewondo; Fakrulloh, Zudan Arief; Riswadi, Riswadi (Pusat Publikasi Nusantara, 2023)
According to Law no. 2 of 2002 concerning safeguarding security and providing community services, protection, protection, and services to the community. This will not be realized if it is not carried out with the discipline of the members of the Police. Deviations in the behavior of Polri members are a violation of the disciplinary regulations of the Polri as stipulated in PP No. 2 of 2003 concerning Disciplinary Regulations for Polri Members. The purpose of writing this journal is the implementation of the implementation of disciplinary law enforcement for members of the Police through disciplinary hearings of the Police, knowing the implementation in the Police disciplinary hearings in realizing a disciplined Police and analyzing optimizing the functions of Police law enforcement in the implementation of disciplinary hearings in order to create a disciplined National Police. It is known that the implementation of disciplinary law enforcement for Polri members through Polri disciplinary hearings is the responsibility of Polri members who violate the law within the corridors of Polri's disciplinary law or violations of the code of ethics, the violation is internally institutional, namely through the trial session and the session of the Professional Code of Ethics Commission. Obstacles in the implementation of the Police disciplinary hearings are changes to the internal legal rules within the National Police, such as the National Police Chief Regulation No. 14 of 2011 concerning the Professional Code of Ethics, previously there were two National Police Chief Regulations governing the same thing, namely the National Police Chief Decree No. Pol: KEP/32 / VII/2003 and Regulation of the Chief of Police, Regulation of the Chief of Police Number 7 of 2006. The new regulation on the Code of Ethics for the Police Profession does not provide sufficient explanation. As a result of regulations that have multiple interpretations, each party will have different controls, so that it can open up opportunities for law enforcement to occur which ultimately creates legal uncertainty